Developing The Community Outreach Effectiveness Model (COEM) for HIV Prevention Among Key Populations in Indonesia: Evidence from The IBBS - Lely Wahyuniar; Aang Sutrisna; Dimas Budi Wicaksana; Rizky Habsi (Faculty of Public Health, Hasanuddin University, Makassar, 2025)
Indonesia continues to experience a concentrated HIV epidemic, with key populations female sex workers, men who have sex with men, transgender women, and people who inject drugs bearing a disproportionate burden, while uptake of HIV prevention services and sustained behavior change remain inadequate. Community outreach has been widely implemented to address these gaps; however, its effectiveness has not been comprehensively documented at the national level. This study aimed to assess the impact of community outreach interventions on HIV prevention uptake and behavioral outcomes among key populations in Indonesia using the Community Outreach Effectiveness Model (COEM). A quantitative retrospective study was conducted using secondary data from the Integrated Bio-Behavioral Survey (IBBS) collected across multiple districts in Indonesia. HIV prevention outcomes were compared between districts with and without community outreach interventions. The study population comprised key populations included in the IBBS, with sample sizes determined by the survey design. Data were collected through structured behavioral questionnaires and biological testing. Multivariable logistic regression analysis was applied to examine associations between exposure to outreach components and HIV testing uptake as well as consistent condom use, and the COEM was developed to operationalize outreach pathways linking inputs to outcomes. The results demonstrated that exposure to community outreach was strongly associated with higher HIV testing uptake across all key populations, with referral by outreach workers showing the greatest effect. Outreach exposure was also significantly associated with improved condom use, particularly through peer-delivered information, free condom distribution, and social media engagement. Combined exposure to multiple outreach components resulted in incremental improvements in both HIV testing uptake and consistent condom use. In conclusion, community outreach functions as a protective factor that strengthens HIV prevention behaviours among key populations in Indonesia, underscoring the need to institutionalize and scale up comprehensive, multi-component outreach strategies within national HIV policies and programs.